Daya Hambat Ekstrak Minyak Atsiri Kulit Buah Jeruk Siam (Citrus nobilis L.) terhadap Pertumbuhan Candida albicans - Oksalani Cahaya Rana; Ayu Mashartini Prihanti; Purwanto Purwanto (Pustaka Kesehatan, 2021)
The high prevalence of oral candidiasis needs special attention. Candida albicans (C. albicans) play a critical role in the progression of deeper oral candidiasis. An effective and safe strategy to control C. albicans activity was needed. The essential oil from siam orange peel has been shown to have antifungal properties. This study aimed to determine the optimal concentration of the essential oils of siam orange peel to inhibit the growth of C. albicans. This is experimental laboratory research with a posttest-only control group design. The water stream was used to get essential oil extract from siam orange peel and made in several concentrations 25%, 50%, 75%, and 100%. The disk diffusion method was applied to determine the inhibition of essential oil extract of siam orange peel to the C. albicans. Nystatin and DMSO 10% plus tween 80 0,5% were used as positive and negative control groups. The results found that the essential oil extract of siam orange peel concentration of 50% and above showed an inhibitory effect on the growth of C. albicans with the most optimal is 75%. The essential oil extract of Siam Orange Peel would be useful as a therapeutic agent to control oral candidiasis.